Workbook como recurso didáctico para el aprendizaje de Química General en los estudiantes de segundo semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Espinoza López, Melany Priscila (2025)
This research aimed to propose the Workbook as a didactic resource for learning General Chemistry among second-semester students of the Pedagogy in Experimental Sciences: Chemistry and Biology program. The problem addressed in this research arose because many of the students at the Universidad Nacional de Chimborazo had not used the Workbook in their learning process; as a result, they did not take full advantage of the benefits offered by this didactic resource. The approach of this study was quantitative with a non-experimental design; it was descriptive and basic research. The type of study was cross-sectional, and data collection involved a population of 40 second-semester students. The technique used was a survey, employing a questionnaire with 10 closed-ended questions as the instrument. After analyzing and interpreting the results, it was concluded that the Workbook was a novel didactic resource for the General Chemistry learning process. It was due to the appealing, dynamic, and interactive content and activities, which favored learning by sparking interest and motivation to learn. This didactic resource was created based on the Flipped Classroom methodology, which fostered an active, dynamic, and interactive learning environment that enriched the educational process.